2003
DOI: 10.1086/375069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Oral Pleconaril for Treatment of Colds Due to Picornaviruses in Adults: Results of 2 Double-Blind, Randomized, Placebo-Controlled Trials

Abstract: The novel capsid-binding antiviral pleconaril inhibits in vitro replication of most rhinoviruses and enteroviruses. Oral pleconaril treatment was studied in 2 parallel randomized, double-blind, placebo-controlled trials. Among 1363 picornavirus-infected participants (65%) in the studies combined, the median time to alleviation of illness was 1 day shorter for pleconaril recipients than for placebo recipients ( ). Cold symptom P ! .001 scores and frequency of picornavirus cultured from nasal mucus specimens wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
181
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(184 citation statements)
references
References 31 publications
3
181
0
Order By: Relevance
“…This model has major advantages as it permits investigations of exacerbations in a controlled manner with a single etiological agent, and facilitates longitudinal sampling, allowing investigation of temporal and quantitative relationships between virus infection, inflammatory mediators, and biological and physiological markers in a manner not possible with cross-sectional studies of naturally occurring exacerbations. The evidence we provide linking rhinovirus infection to COPD exacerbations should stimulate research into both existing and novel antiviral therapies as potential therapies in COPD (44). Therapies targeting neutrophilic inflammation (45) and neutrophil elastase inhibitors (46) or augmentation of IFN-b may also have potential in the treatment or prevention of COPD exacerbations.…”
Section: Discussionmentioning
confidence: 93%
“…This model has major advantages as it permits investigations of exacerbations in a controlled manner with a single etiological agent, and facilitates longitudinal sampling, allowing investigation of temporal and quantitative relationships between virus infection, inflammatory mediators, and biological and physiological markers in a manner not possible with cross-sectional studies of naturally occurring exacerbations. The evidence we provide linking rhinovirus infection to COPD exacerbations should stimulate research into both existing and novel antiviral therapies as potential therapies in COPD (44). Therapies targeting neutrophilic inflammation (45) and neutrophil elastase inhibitors (46) or augmentation of IFN-b may also have potential in the treatment or prevention of COPD exacerbations.…”
Section: Discussionmentioning
confidence: 93%
“…At the first study visit, subjects were taught to collect samples of their own nasal mucus, using a nose-blowing technique as previously described (10,11). These samples were analyzed for common respiratory viruses by multiplex polymerase chain reaction (respiratory MultiCode assay; EraGen Biosciences, Madison, WI) (12) and by seminested polymerase chain reaction specific for the hemagglutinin gene of the 2009 H1N1 influenza virus (see the online supplement for details).…”
Section: Procedures and Definitionsmentioning
confidence: 99%
“…The agent that came furthest in clinical development was pleconaril. In two large phase II, placebo-controlled, natural cold trials, pleconaril was demonstrated to reduce the time to alleviation of illness in patients with an onset of a typical cold within 36 hours of respiratory symptoms during the months between July and December; this clinical response was noted in subjects who were HRV positive (121). Furthermore, subsequent analyses confirmed that clinical response to pleconaril was limited to those infected with pleconaril-sensitive HRV strains (122).…”
Section: Pathogen-specific Therapymentioning
confidence: 91%
“…Induction of reduced pleconaril susceptibility in HRV isolates was seen in greater than 10% of patients, although the clinical course of illness in these subjects was less protracted than in the overall group. A subsequent 6-week prophylaxis study documented that pleconaril induced CYP3A4, which led to intermenstrual bleeding and related menstrual abnormalities in women taking estrogenbased oral contraceptives (121,123). In March 2002, a U.S. Food and Drug Administration Antiviral Drugs Advisory Committee voted to not recommend pleconaril approval based on these drug interactions and possible transmission of resistance isolates.…”
Section: Pathogen-specific Therapymentioning
confidence: 99%
See 1 more Smart Citation